ANALISIS KOMPARASI KUALITAS LAYANAN DAN HARGA ANTARA SHOPEE DAN TOKOPEDIA - Fiqih Harso, Gissely (GEMAH RIPAH: Jurnal Bisnis, 2022)
This study was conducted to determine whether there is a difference between service quality and price in two online shopping applications, namely Shopee and Tokopedia. The type of research that the author does is research using quantitative research methods with this type of research, namely comparative research. Comparative research is research that is used to compare between two or more groups of a certain variable. This research was conducted by distributing questionnaires to respondents who had shopped at the Shopee and Tokopedia applications. The sampling technique used in this study is non-probability sampling, which is a non-random sampling technique using purposive sampling, where the sample is selected based on its characteristics. Using analysis of homogeneity test, t-test difference test. The homogeneity test serves to determine whether or not the variance is uniform in each sample to be taken, while the t-test difference test serves to test the hypothesis about whether there is a significant difference between the two sample groups by means of a mean difference.